2020
DOI: 10.1186/s13063-020-04388-x
|View full text |Cite
|
Sign up to set email alerts
|

Using systematic data categorisation to quantify the types of data collected in clinical trials: the DataCat project

Abstract: Background: Data collection consumes a large proportion of clinical trial resources. Each data item requires time and effort for collection, processing and quality control procedures. In general, more data equals a heavier burden for trial staff and participants. It is also likely to increase costs. Knowing the types of data being collected, and in what proportion, will be helpful to ensure that limited trial resources and participant goodwill are used wisely. Aim: The aim of this study is to categorise the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Although only data that is used for outcomes should be collected, we recognise this is not always the case, with additional non-critical data commonly being collected. This has been confirmed by the recently published DataCat project which concluded that a substantial amount of data collection is not related to trial outcomes [18]. In trials that have altered their data collection processes and methods, initial feedback suggests participants have responded favourably, though in many cases it is too early to formally evaluate the impact upon participant retention.…”
Section: Data Collectionmentioning
confidence: 91%
“…Although only data that is used for outcomes should be collected, we recognise this is not always the case, with additional non-critical data commonly being collected. This has been confirmed by the recently published DataCat project which concluded that a substantial amount of data collection is not related to trial outcomes [18]. In trials that have altered their data collection processes and methods, initial feedback suggests participants have responded favourably, though in many cases it is too early to formally evaluate the impact upon participant retention.…”
Section: Data Collectionmentioning
confidence: 91%
“…With a standardized taxonomy from our mammal supertree (Upham et al, 2019), we used the phylofactor package to partition infection status and prevalence as binomial responses in a series of GLMs (Washburne et al, 2019). We included the total number of hosts sampled in the former as weights to account for uneven sampling effort (Crowley et al, 2020), and we determined the number of significant mammal clades in both models using Holm's sequentially rejective test with a 5% family-wise error rate.…”
Section: Accepted Articlementioning
confidence: 99%
“…The collection of non-essential data has long been known to increase the burden on both participating sites and sponsors, and this is now starting to be quantified. Recent data from Fougerou-Leurent et al [ 14 ] suggest that only 13% of the data collected are critical data items and Crowley et al [ 15 ] found 5% of items were for the primary outcome of the trial.…”
Section: Minimising Datamentioning
confidence: 99%